Study on male secondary genitalia of seven species of orthetrum newman (Odonata: Libellulidae) in Peninsular Malaysia - Hanisah, A.; Ng, Y.F.; Choong, C.Y. (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
Seven Orthetrum Newman, 1833 species occurring in Peninsular Malaysia have been described, in this paper we focus on describing the details of male secondary genitalia of the seven Orhetrum species i.e. anterior lamina, hamule and vesica spermalis. The structure of anterior lamina and its setae are good taxonomic characters to distinguish the Orthetrum species.